Samarbejdet mellem den danske kriminalforsorg og den frivillige sektor: – fra ikke-formaliseret samarbejde til strategiske samarbejdspartnere - Olesen, Anette (Nordisk Tidsskrift for Kriminalvidenskab, 2022)
Abstract The Danish Prison and Probation Service (DPPS) is facing prison overcrowding, staff shortages and a political focus on order and control. This situation is challenging prisons in fulfilling their rehabilitative function. Delivery of rehabilitation services in the DPPS from external voluntary organisations is therefore of interest and a strategic, systematic collaboration between the DPPS and the voluntary sector has been included in DPPS agreements that describe the financial framework and the operational and developmental targets to be realised during the contractual period 2022-25. Knowledge about the current collaboration and its potential is nevertheless scarce. This study explores the present informal collaboration between voluntary organisations delivering in/post-prison rehabilitative programmes and the DPPS, with a focus on funding structures and collaboration demands. The study is based on semi-structured interviews with prison and probation staff and representatives from voluntary organisations as well as participant observation of volunteer training in/post prison. The findings reveal that the rehabilitative work of volunteers in prisons is challenged by, among other things, the focus placed by the DPPS on professionalism, standardisation and impact measurement. Moreover, lobbying for funding is found to be time-consuming and challenging to the autonomy of voluntary organisations. The article supports protecting the voluntary organisations’ diversity of methods and approaches to prisoner rehabilitation.